Copying Chalkokondyles : Greek manuscript production in 16th- century Venice - Kurtoğlu, Ferhat Sezer. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2023., 2023)
Laonikos Chalkokondyles, one of the four contemporary Byzantine historiographers of the fall of Byzantium, composed his work in the early 1460s after the advancing Ottomans captured Constantinople and the remnants of the Byzantine Empire. His Herodotean treatise, the Demonstrations of Histories (Apodeixis Historion), gained considerable popularity in manuscript form during the first half of the 16th century before a Latin translation appeared in print in Basel in 1556. Two-thirds of 32 extant manuscripts are known or are likely to have been produced in Venice between 1540 and 1550. The purpose of the thesis is to contextualize this extensive copying activity centered in Venice around the 1540s. It will first examine the manuscript tradition of the Histories and the paratextual evidence found in manuscripts, then scrutinize the overall production output of the scribes and the collections of patrons or book merchants who were in possession of the manuscripts in question, and finally inspect the connections between the copyists and the patrons. By discovering the intellectual spaces in which the manuscripts of the Histories were placed, the study will reveal economic, social, and intellectual tendencies in mid-16th-century Venice that popularized the Greek manuscripts of Laonikos Chalkokondyles’ narrative of the fall of Byzantium and the rise of the Ottomans.
Keywords: Chalkokondylēs, Laonikos, approximately 1430-approximately 1490.; Chalkokondylēs, Laonikos, ca. 1430-ca. 1490. Apodeixeis historiōn; Byzantine Empire -- History -- 1081-1453.